OP0235 Genetic Risk Factors in Idiopathic Inflammatory Myopathies Are Shared with Other Autoimmune Disorders in European Populations. (10th June 2014) - Jani, M.; Massey, J.; Wedderburn, L.; Vencovský, J.; Danko, K.; Lundberg, I.; Selva-O'Callaghan, A.; Radstake, T.; Platt, H.; Warren, R.; Griffiths, C.; Padyukov, L.; et al.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) may present as a primary disorder, or may overlap with connective tissue diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) or systemic sclerosis. The aetiology of IIM is largely unknown, but is thought to include a combination of genetic and environmental factors. To generate ethnically homogeneous IIM cohorts of sufficient size given its rarity, one of the largest European IIM initiatives has enabled Europe wide ascertainment of cases with EUMYONET. Numerous genome-wide association studies (GWAS) have identified many genetic variants associated with autoimmune disorders, several common to multiple disorders. This is supported by our recent dermatomyositis (DM) GWAS, suggesting genetic overlap with other autoimmune disorders 1 . Objectives: We sought to identify additional novel genetic risk factors in adult and juvenile polymyositis (PM) and DM (not previously identified by DM GWAS), shared with other autoimmune disorders. Methods: SNPs significantly associated with SLE, RA, juvenile idiopathic arthritis, coeliac disease, Crohn's disease, ulcerative colitis, psoriasis, type 1 diabetes, multiple sclerosis or systemic sclerosis were identified from published Caucasian GWAS and from the national human genome research institute catalogue of published GWAS. 233 unique SNPs were identified ( p <5×10 -8 ), of which 99 had not been directly genotyped or captured through our MYOGEN GWAS 1 . SNPs were genotyped by Sequenom in a sample of 1001 European Caucasian individuals with definite or probable adult or juvenile PM or DM. 83 SNPs passed quality control criteria. GWAS data from EU contributors was imputed to the 1000G_phase1integrated_v3 reference panel. Association tests for IIM subgroups and random-effects meta-analysis of the individual country datasets were performed. Results: Samples with >5% missing genotype data were excluded, resulting in 1149 cases and 3572 controls. Outside the MHC region, a non-synonymous SNP rs2304256 in the TYK2 gene was identified reaching Bonferroni-corrected significance in IIM and DM (β= -0.21, p value=0.00027; β= -0.25, p value=0.00020 respectively). Two further SNPs within the BLK gene and 2335bp 5' of BLK were associated with DM (rs2618476, β=0.24, p value=0.00062; rs13277113, β=0.25 p value=0.00045 respectively) but not with PM, supporting the results of our DM GWAS. Conclusions: We have identified TYK2 as a novel association for DM, suggesting genetic overlap of DM with other autoimmune disorders, and indicating genetic heterogeneity between PM and DM. TYK2 has been associated previously with SLE, type 1 diabetes and multiple sclerosis. Further associations of the BLK gene with DM, suggests a role of B cells in its development. References: Miller FW et al. Arthritis Rheum. 2013 Dec; 65(12):3239-3247 Acknowledgements: Funding: Arthritis Research UK (grants 18474; 14518), Intramural Research Program of the NIH, Wellcome Trust (076113; 085860). We thank all other members of the EUMYONET and Myositis Genetics Consortium (MYOGEN). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2877